COVID-19 Vaccination and Risk of Post–COVID-19 Cardiovascular Disease: A Population-Based Cohort and Target Trial Emulation Study - Binyam Tariku Seboka; Dianna J Magliano; Thomas H Marwick; Quan Huynh (European Heart Journal - Quality of Care and Clinical Outcomes, 2026)
Abstract Background Whether COVID-19 vaccination is associated with lower long-term cardiovascular risk after SARS-CoV-2 infection and how much infection prevention mediates this association remain unclear. Objective To evaluate associations of vaccination, including its timing relative to SARS-CoV-2 infection, with post-COVID-19 cardiovascular disease (CVD), and quantify the contribution of infection prevention. Methods This statewide population-based cohort study used linked administrative health data for 2,391,456 adults in Victoria, Australia (2019–2025). Associations of pre- or post-infection vaccination with major adverse cardiovascular events (MACE; primary outcome), stroke, heart failure, acute myocardial infarction (AMI), acute coronary syndrome (ACS), atrial fibrillation (AF), and venous thromboembolism (VTE) were evaluated using time-varying Cox proportional hazards regression, causal mediation analysis, and target trial emulation. Results Vaccination was associated with lower hazards of MACE and all secondary outcomes. Estimated absolute risk reductions for MACE were 0.21% with pre-infection vaccination and 0.24% with post-infection vaccination. Three or more vaccine doses were associated with progressively lower hazards across cardiovascular outcomes. Mediation analysis suggested that approximately 68% of the estimated association between vaccination and lower post-COVID cardiovascular risk was not explained by prevention of SARS-CoV-2 infection. Conclusion Vaccination before or after SARS-CoV-2 infection was associated with lower hazards of post-COVID-19 cardiovascular outcomes, with stronger observed associations at higher dose numbers. Most of the estimated association was not explained by infection prevention alone. These findings support COVID-19 vaccination as an important component of strategies to reduce the burden of post-COVID-19 CVD while highlighting the need for further studies to clarify the mechanisms underlying these associations.